2022
DOI: 10.3847/1538-4357/ac78ea
|View full text |Cite
|
Sign up to set email alerts
|

Reading the CARDs: The Imprint of Accretion History in the Chemical Abundances of the Milky Way's Stellar Halo

Abstract: In the era of large-scale spectroscopic surveys in the Local Group, we can explore using chemical abundances of halo stars to study the star formation and chemical enrichment histories of the dwarf galaxy progenitors of the Milky Way (MW) and M31 stellar halos. In this paper, we investigate using the chemical abundance ratio distributions (CARDs) of seven stellar halos from the Latte suite of FIRE-2 simulations. We attempt to infer galaxies’ assembly histories by modeling the CARDs of the stellar halos of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 107 publications
2
11
0
Order By: Relevance
“…All The resolution of this suite of simulations enables baryonic subhalos to be well-resolved even near each MW-like galaxy. It also resolves the formation of tidal streams from satellite galaxies down to approximately 10 8 M e in total mass or 10 6 M e in stellar mass (at z = 0), similar to that of the MW's "classical" dwarf spheroidals (e.g., Panithanpaisal et al 2021;Cunningham et al 2022;Shipp et al 2022). Furthermore, dark matter particles in each snapshot are processed with Rockstar (Behroozi et al 2013a) to produce halo catalogs that are connected in time using consistent trees to form a merger tree (Behroozi et al 2013b).…”
Section: Simulationsmentioning
confidence: 71%
See 3 more Smart Citations
“…All The resolution of this suite of simulations enables baryonic subhalos to be well-resolved even near each MW-like galaxy. It also resolves the formation of tidal streams from satellite galaxies down to approximately 10 8 M e in total mass or 10 6 M e in stellar mass (at z = 0), similar to that of the MW's "classical" dwarf spheroidals (e.g., Panithanpaisal et al 2021;Cunningham et al 2022;Shipp et al 2022). Furthermore, dark matter particles in each snapshot are processed with Rockstar (Behroozi et al 2013a) to produce halo catalogs that are connected in time using consistent trees to form a merger tree (Behroozi et al 2013b).…”
Section: Simulationsmentioning
confidence: 71%
“…The first step involves inspecting the density distribution of star particles in each simulation in the age-formation distance plane at z = 0, first introduced in Cunningham et al (2022) and Khoperskov et al (2022a), as shown in Figure 1. Here, star particle ages are shown on the x-axis, and the formation distance of star particles (defined as the distance of the star particle at its formation time from the center of the main MWlike host) is on the y-axis.…”
Section: Identifying Accretion Events In the Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our clearest view into this hierarchical assimilation comes from the stellar halo of the Milky Way, which is almost entirely comprised of debris from accretion events (e.g., Di Matteo et al 2019;Mackereth & Bovy 2020;Naidu et al 2020). Families of halo stars that arrived as part of the same galaxy retain similar phase space properties (e.g., energies, angular momenta, actions; Brown et al 2005;Gómez et al 2013;Simpson et al 2019) as well as shared chemical abundance patterns (e.g., Lee et al 2015;Cunningham et al 2022). With detailed chemodynamical data, it is challenging (e.g., Jean-Baptiste et al 2017) but possible to determine which populations of stars were originally associated with the same dwarf galaxy merger event.…”
Section: Introductionmentioning
confidence: 99%